Development of Realistic Mathematics Education Based Mathematics Learning Tools to Improve Problem Solving Skills - Fadilah, Putri; Panomram, Waratchaya (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop mathematics learning tools based on the Realistic Mathematics Education approach for comparison material in Grade VII junior high school. Methodology: The development process followed the 4-D model, consisting of the define, design, and develop stages. The research subjects were students of class VII-B at Al-Hidayah Junior High School Medan. To evaluate the quality of the developed learning tools, expert validation sheets were used to measure validity, while student response questionnaires were employed to assess practicality. Main Findings: The findings indicate that all developed learning tools met the established validity criteria with very good classifications. The Learning Implementation Plan achieved an average score of 4.50 out of 5.00, while the Teaching Materials obtained an average score of 4.60. The Student Worksheets reached an average score of 4.52, and the Learning Media recorded an average score of 4.50, all categorized as very good. In addition, the Learning Outcome Tests achieved an average score of 4.53 out of 5.00, confirming their strong validity. The practicality of the learning tools was also highly supported by students, as reflected in the student response questionnaire, which yielded an average score of 4.88 out of 5.00 with very good criteria. Novelty/Originality of this study: This research offers a new contribution by combining RME principles and adaptive learning tool design, to create relevant and contextual learning experiences to support students' critical thinking skills.